Memahami Hambatan dan Cara Lansia Mempelajari Media Sosial - Ashari, Rizqi Ganis (FISIP Universitas Atma Jaya Yogyakarta, 2018)
This article aims to understand the various barriers and experiences of elderlies in learning how to use social media as part of their lives. For that purposes, an in-depth interview was conducted through qualitative method with phenomenology approach on two senior informants in Semarang area. The results of the study indicate the elderly are experiencing: (1) intrapersonal, (2) structural and (3) functional barriers. Intrapersonal barriers are overcome by social factors, whereas structural and functional obstacles are overcome by individual factors. It is also found that the overall elderly’s effort to adopt social media emerged out of necessity..